Circadian rhythms in colonic function - Hibberd, Timothy J.; Ramsay, Stewart; Spencer-Merris, Phaedra; Dinning, Phil G.; Zagorodnyuk, Vladimir P.; Spencer, Nick J. (Frontiers in Physiology, 2023)
A rhythmic expression of clock genes occurs within the cells of multiple organs and tissues throughout the body, termed ‘peripheral clocks’. Peripheral clocks are subject to entrainment by a multitude of factors, many of which are directly or indirectly controlled by the light-entrainable clock located in the suprachiasmatic nucleus of the hypothalamus. Peripheral clocks occur in the gastrointestinal tract, notably the epithelia whose functions include regulation of absorption, permeability, and secretion of hormones; and in the myenteric plexus, which is the intrinsic neural network principally responsible for the coordination of muscular activity in the gut. This review focuses on the physiological circadian variation of major colonic functions and their entraining mechanisms, including colonic motility, absorption, hormone secretion, permeability, and pain signalling. Pathophysiological states such as irritable bowel syndrome and ulcerative colitis and their interactions with circadian rhythmicity are also described. Finally, the classic circadian hormone melatonin is discussed, which is expressed in the gut in greater quantities than the pineal gland, and whose exogenous use has been of therapeutic interest in treating colonic pathophysiological states, including those exacerbated by chronic circadian disruption.